Educational processes and practices of amerindian people in Brazil a perspective on contemporary research - Bergamaschi, Maria Aparecida (Education Policy Analysis Archives, 2012)
The indigenous education in Brazil and the Americas has been growing and changing its characteristics over the past decades, raising some questions: what characterizes a school as indigenous, specific and differentiated? What are the meanings of this institution for the different indigenous peoples and for the different amerindian communities? What relation exists between indigenous schools and the process that forms and affirms ethnic identities? What paths need to be built to form indigenous teachers? Based on these questions, this article analyzes 179 master's and doctoral research projects conducted over the past decade which have been published on the CAPES website: 135 were master's and 44 Ph.D. thesis. We searched for papers looking for "indigenous education" as the keyword and analyzed especially the abstracts. Among other things, we emphasize the themes and theoretical methodological approaches of these investigations which, from their multiple perspectives, reveal a growing ethical and aesthetical attention to Amerindian education and schools.